Greener preparation of a flexible material based on macaw palm oil derivatives and CO2 - Alarcon, Rafael Turra; Gaglieri, Caroline [UNESP]; Bannach, Gilbert [UNESP]; Cavalheiro, Éder Tadeu Gomes (Royal Society of Chemistry (RSC), 2024)
Carbonated macaw palm oil and maleinised macaw palm oil were reacted with five different amines to obtain renewable copolymers with a bio-based content greater than 80%. The polymerisation process is greener and reduces parallel reactions in the glycerol ester backbone. Polymerisation was completed in only 24 h at 120 °C. Polymers demonstrated flexible properties and were in a rubbery state at room temperature. The polymer using 1,6-hexanediamine-HDA showed hydrophobicity and could be a promising coating for wood that can be used for industrial applications. Moreover, all polymers were totally hydrolysed in a sodium hydroxide solution.